HIV nucleocapsid proteins as targets for novel 1,2-benzisothiazol-3(2H)-one benzenesulfonamides: synthesis and antiretroviral activity - Loddo, Roberta; Incerti, Matteo; Favari, Elda; Manca, Valeria; Cogoni, Marta; Piras, Rebecca; Virdis, Luca; Palmas, Vanessa; Tamburini, Elena; La Colla, Paolo; Sanna, Giuseppina (Frontiers in Microbiology, 2025)
A new class of 1,2-benzisothiazol-3(2H)-one benzenesulfonamides has been synthesized. In cell-based assays, the lead compound 6 inhibits the replication of HIV-1, HIV-2, and HIV-1 variants carrying clinically relevant mutations against non-nucleoside, nucleoside, and protease inhibitors. In enzyme assays, compound 6 does not inhibit HIV-1 reverse transcriptase and integrase. Genome sequencing of HIV-1 mutants selected for resistance to compound 6 reveals no mutations in the pol or env genes. Instead, two mutations are mapped in the gag region, which encodes nucleocapsid (NC) proteins involved in early and late key processes of retrovirus replication, suggesting that NC proteins are the target of the title compounds. Compound 6 shows concentration-dependent virucidal activity against cell-free HIV-1 and HIV-2. Benzisothiazol-3(2H)-one benzenesulfonamides are a new class of antiretroviral agents with an intriguing spectrum and mode of action.